Role of binaural hearing in speech intelligibility and spatial release from masking using vocoded speech - Garadat, Soha N. (Acoustical Society of America, 2009)
A cochlear implant vocoder was used to evaluate relative contributions of spectral and binaural temporal fine-structure cues to speech intelligibility. In Study I, stimuli were vocoded, and then convolved through head related transfer functions (HRTFs) to remove speech temporal fine structure but preserve the binaural temporal fine-structure cues. In Study II, the order of processing was reversed to remove both speech and binaural temporal fine-structure cues. Speech reception thresholds (SRTs) were measured adaptively in quiet, and with interfering speech, for unprocessed and vocoded speech (16, 8, and 4 frequency bands), under binaural or monaural (right-ear) conditions. Under binaural conditions, as the number of bands decreased, SRTs increased. With decreasing number of frequency bands, greater benefit from spatial separation of target and interferer was observed, especially in the 8-band condition. The present results demonstrate a strong role of the binaural cues in spectrally degraded speech, when the target and interfering speech are more likely to be confused. The nearly normal binaural benefits under present simulation conditions and the lack of order of processing effect further suggest that preservation of binaural cues is likely to improve performance in bilaterally implanted recipients.